Integrasi Nilai-Nilai Moderasi Beragama Dalam Pembelajaran Peradaban Islam Fakultas Bisnis Islam Syariah UIN Sunan Kalijaga Yogyakarta - Khoirotul Muslimah; Ibi Satibi; Sabarudin Sabarudin; Farhati Farhati (LP. Ma'arif Janggan Magetan, 2023)
Religious Moderation Values ​​are a manifestation of moderation in various forms of interaction. This study discusses the integration of the moderation value of religion in Islamic Civilization courses including the Semester Learning Design (RPS) as well as the integration of the value of moderation in religion among students and lecturers at FEBI UIN SUKA. The research method uses a descriptive qualitative approach so as to provide a complete description and analysis of various case studies. The data collected was obtained by in-depth interview methods, direct observation and literature study. To test the validity by means of source and technique triangulation. The research results show the following. First, the integration of the values ​​of religious moderation based on the Semester Lesson Plan obtained moderation values ​​in the form of a fair attitude (not one-sided) and understanding diversity in tolerance between religions and local cultures. Second, the integration of moderation values ​​in learning in the form of making Semester Learning Plans (RPS) based on moderation values. Third, the integration of moderation values ​​when lecturers deliver Islamic Civilization courses, almost all material is associated with religious moderation values ​​such as moderation, love of peace, and understanding diversity or tolerance among people. Fourth, the integration of the values ​​of moderation when students have discussions is manifested by upholding democratic elements, namely being free to give opinions and being ready to accept any decision without coercion.